Microbiome in lung explants of idiopathic pulmonary fibrosis: a case–control study in patients with end-stage fibrosis. Issue 5 (11th August 2017) - Kitsios, Georgios D; Rojas, Mauricio; Kass, Daniel J; Fitch, Adam; Sembrat, John C; Qin, Shulin; Veraldi, Kristen L; Gibson, Kevin F; Lindell, Kathleen; Pilewski, Joseph M; Methe, Barbara; Li, Kelvin; et al.
Abstract : The microbiome has been proposed to play a role in the progression of idiopathic pulmonary fibrosis (IPF) based on bronchoalveolar lavage analyses, but the microbiome of lung tissue in IPF has not been explored. In a case–control study of lung explants analysed by 16S rRNA gene sequencing, we could not reliably detect bacterial DNA in basilar tissue samples from patients with either chronic or acute exacerbations of IPF, in contrast to control candidate-donor lungs or cystic fibrosis explants. Thus, our data do not indicate microbiome alterations in regions of IPF lung with advanced fibrosis.